Determination of the Principal Parameter of Ultrasonic Pulse Velocity and Compressive Strength of Lightweight Concrete by Using Variance Method (vol 44, pg 639, 2008) - Tanyildizi, Harun; Coskun, Ahmet (Maik Nauka/Interperiodica/Springer, 2017)
[Abstract Not Available]